2013
DOI: 10.1369/0022155413483574
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Expression and Localization of Diacylglycerol Kinase Isozymes in Rat Retina

Abstract: Recent studies have revealed that phosphoinositide (PI) signaling molecules are expressed in mammalian retinas, suggesting their importance in its signal transduction. We previously showed that diacylglycerol kinase (DGK) isozymes are expressed in distinct patterns in rat retina at the mRNA level. However, little is known about the nature and morphological aspects of DGKs in the retina. For this study, we performed immunohistochemical analyses to investigate in the retina the expression and localization of DGK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 75 publications
(113 reference statements)
1
12
0
Order By: Relevance
“…Gene expression profiling of a mouse brain has shown that DGKa is expressed throughout the entire brain (17). In the retinas, DGKa is also expressed in ganglion cells in the ganglion cell layer (GCL) and inner plexiform layer (IPL) (18).…”
Section: Dgkamentioning
confidence: 99%
See 4 more Smart Citations
“…Gene expression profiling of a mouse brain has shown that DGKa is expressed throughout the entire brain (17). In the retinas, DGKa is also expressed in ganglion cells in the ganglion cell layer (GCL) and inner plexiform layer (IPL) (18).…”
Section: Dgkamentioning
confidence: 99%
“…In the retinas, DGKb is strongly expressed in the rod and cone bipolar cells and horizontal cells of the outer plexiform layer (OPL) and moderately expressed in the inner nuclear layer (INL) and IPL (18).…”
Section: Dgkbmentioning
confidence: 99%
See 3 more Smart Citations